A satisfação do consumidor dos supermercados de vizinhança, na cidade de Fortaleza - Silva, Pedro Marcos de Oliveira (2007)
The present work was carried through in the city of Fortaleza-CE, and has objective to analyze the satisfaction level, from the point of view of the consumer's of the quality of the services offers the all services for the neighborhood supermarkets. A study of exploration nature was applied, using a bibliographical referential, of classic of the marketing, reviewed and periodic authors specific, discoursing the theories that contemplate the retail, and particularly the supermarkets. Field research was also carried through, with the primary data collecting through, application of questionnaires with sample of 400 consumers, that analyzed its level of satisfaction and the variables used for the consumer, for effect of definition of the supermarket. The gotten results, from this work of research, had been enough for attainment of its objectives. The consumers had demonstrated a satisfaction feeling, have even so not reached the excellency, how much the quality of the mix of services that the supermarkets disponibilization, considering it positive and similar to the existing ones in the great nets, exerting great influences in its decisions of purchase. The conclusions that had been extracted had signaled that the neighborhood supermarket is consolidated therefore the consumers is answering positively to this format of store and that the excellent factors, for the definition of the supermarket, orderly, of priority are prices, localization and variety of products.